Henri Nouwen: Deeply Wounded and Beloved Healer - Graves, Thomas H. (2022)
This article tracks the life of Henri Nouwen focusing on his years at Yale Divinity School, particularly 1972-73 when he taught a course on Thomas Merton in which the author participated. The author recounts his interaction with Nouwen both personally and academically. Following Yale, the article describes Nouwen’s immersion in Latin American liberation theology, his teaching at Harvard Divinity School, and eventually finding his vocational calling fulfilled at a L’Arche community, Daybreak, in Toronto. Henri’s ministry to the profoundly disabled at Daybreak turned tragic as his workaholic schedule of ministry, speaking and writing was disrupted by a wintertime accident. Amidst this Henry was forced to deal with his own profound insecurity and depression stemming in part from his homosexuality, which he kept hidden. An analysis of his book, The Return of the Prodigal Son, demonstrates how Henri used his own anxieties, doubts and failures to bring spiritual growth and healing to a global audience. Henri’s hectic lifestyle and psychological stress finally brought the life of this deeply wounded and beloved healer to an early end.
Keywords: Psychology; Pastoral Theology; Disability; Spirituality; L’Arche